2020
DOI: 10.1080/22221751.2020.1729068
|View full text |Cite
|
Sign up to set email alerts
|

Penaeidins restrict white spot syndrome virus infection by antagonizing the envelope proteins to block viral entry

Abstract: Emerging studies have indicated that some penaeidins restrict virus infection; however, the mechanism(s) involved are poorly understood. In the present study, we uncovered that penaeidins are a novel family of antiviral effectors against white spot syndrome virus (WSSV), which antagonize the envelope proteins to block viral entry. We found that the expression levels of four identified penaeidins from Litopenaeus vannamei, including BigPEN, PEN2, PEN3, and PEN4, were significantly induced in hemocytes during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Anti-microbial peptides (AMPs) are a broad family of peptides found widely in nature [ 50 ] and are an essential part of the innate immune response. These molecules have been shown to boost the performance of livestock animals [ 24 , 51 ] and shrimp more specifically [ 52 ], and indeed recently evidence of AMPs restricting infection of WSSV was shown in L. vannamei [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-microbial peptides (AMPs) are a broad family of peptides found widely in nature [ 50 ] and are an essential part of the innate immune response. These molecules have been shown to boost the performance of livestock animals [ 24 , 51 ] and shrimp more specifically [ 52 ], and indeed recently evidence of AMPs restricting infection of WSSV was shown in L. vannamei [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Xiao et al’s research, WSSV infection activates the Toll and IMD (NF-κB-related) signalling pathways that induce the production of penaeidins, including BigPEN, PEN2, PEN3, and PEN4. Specifically, PEN2 interferes with the ability of the receptor-binding protein VP24 to bind to the host receptor LvpIgR, thereby blocking viral entry into the target cells [ 35 ]. The real-time PCR data showed that the rVP24-fed maggot carried rVP24 to the digestive tract of the shrimp, where it successfully induced a specific immune gene response.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of LvFoxP decreased expression of most immune effector proteins analyzed in this study, including CTLs, lysozyme, hemolin, PPOs, and AMPs from ALF, PEN, and Crustin families, which are all essential for humoral immune responses. Previous studies have described that PENs, ALFs and SWDs, and secreted immune functional proteins hemolin and CTLs possess both antibacterial and antiviral activities in shrimp ( 25 , 28 , 32 , 33 ). It can be inferred that through up-regulating expression of these proteins, LvFoxP may enhance immune responses in shrimp.…”
Section: Discussionmentioning
confidence: 99%